Strategi Komunikasi Pemasaran Coffee Shop Kaze Headquarter Melalui Bauran Pemasaran Dalam Mempertahankan Daya Beli Konsumen - Putri, Deftiyani Rachmawati; Dharta, Firdaus Yuni; Oxcygentri, Oky (CV. ITTC INDONESIA, 2024)
In one coffee shop, new concepts are often discussed that make the appeal of a modern coffee shop. At a time when competition in the coffee shop business is increasingly fierce, Kaze Headquarter is trying to maintain its own brand to maintain consumer purchasing power. This research aims to determine Kaze Headquarter's marketing communication strategy in maintaining consumer purchasing power and also introducing its own brand to the public. Strategy is essentially planning to achieve a goal. This research uses a marketing mix in promotional programs. This study uses a qualitative method. The subjects in this research were those who actually worked at Kaze Headquarters, one Kaze Headquarters manager, one Kaze Headquarters bartender, one Kaze Headquarters Barista, and one Kaze Headquarters waiter who acted as an informant. This research concluded that Kaze Headquarter carried out a communication strategy using a marketing mix by creating attractive promos. This is done with the aim of maintaining consumer purchasing power and increasing customer interest in coming. Kaze headquarter's relationship with consumers and the community is needed to create a good name and image and also gain consumer trust.